1979
DOI: 10.1021/jo00394a004
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of structure and transannular interactions in a series of cage compounds

Abstract: A series of cage systems with general structure 7 were synthesized. By variation of bridge C, the distance between functional groups A and B could be changed systematically and the chemical consequences of these changes investigated. Thus, Diels-Alder reactions between benzoquinone and cyclic dienes ranging from cyclobutadiene to cycloheptadiene, and including cyclooctatetraene, yielded endo dienes which were subsequently converted to cage structures photochemically. This transformation results in compounds 8,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

1981
1981
2005
2005

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…On the other hand, the synthesis and chemistry of heterocyclic cage compounds have received less attention. However, there are some reports regarding the chemistry and synthesis of oxa cage compounds in the literature. This class of heterocyclic cages is synthesized by intramolecular alkene−oxirane (2σ−2π) photocycloaddition, by transannular cyclization of suitable compounds, by tandem cyclization, by dehydration of diols having the proper stereochemistry, by base-promoted rearrangement, and by intramolecular etherification of the alkene bond with organoselenium reagents …”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the synthesis and chemistry of heterocyclic cage compounds have received less attention. However, there are some reports regarding the chemistry and synthesis of oxa cage compounds in the literature. This class of heterocyclic cages is synthesized by intramolecular alkene−oxirane (2σ−2π) photocycloaddition, by transannular cyclization of suitable compounds, by tandem cyclization, by dehydration of diols having the proper stereochemistry, by base-promoted rearrangement, and by intramolecular etherification of the alkene bond with organoselenium reagents …”
Section: Introductionmentioning
confidence: 99%
“…~~ In our hantls, the thermal c!-cloacltlition was not successful, but Barbor:tk ct aZ. 32 have recently reported that low yields may be obtained by heating the reactant. ; a t 50" for 2.5 weeks.…”
mentioning
confidence: 68%
“…There are some reports regarding the chemistry and synthesis of oxa-cage compounds in the literature. This class of heterocyclic cage compounds is synthesized by intramolecular alkene−oxirane (2σ−2π) photocycloaddition, by transannular cyclization of suitable compounds, by tandem cyclization, by dehydration of diols having the proper stereochemistry, by base-promoted rearrangement, and by intamolecular etherification of an alkene bond with organoselenium reagents .…”
Section: Introductionmentioning
confidence: 99%